The Effectiveness Use of Virtual Reality Media in Physics Education of Solar System Towards Cognitive Learning Outcomes - Sigit Dwi Saputro; Agung Setyawan (Jurnal Pendidikan Indonesia, 2020)
Digital literacy skills in the context of mastering the use of digital media were needed to streamline achievements in learning. One of the digital medias that can be applied in abstract learning is virtual reality. The purpose of this research was to determine the effectiveness of cognitive learning outcomes which include the presence or absence of the influence of the use of virtual reality media, the completeness of learning outcomes based on KKM and the completeness of classical learning outcomes. This type of research was pre-experimental by using one group pre-test post-test design. The sample used was class VIII Al-Asyari Technology Middle School which consists cof only one class. The instruments used in the study include description tests. The effect of learning outcomes was analyzed by t-test using SPSS, learning outcomes will be analyzed based on the Minimum Completion Criteria (KKM) and classical completeness while learning motivation was analyzed quantitatively. The results showed that physics learning using effective virtual reality media on learning outcomes as evidenced by the influence of virtual reality media on results with a significance of 0.000, learning outcomes reached the KKM value of 75 with an average yield of 88.1. Classical learning completeness obtained a percentage of results of 86.3% included in the excellent category.